Indole Synthesis by Rhodium(III)‐Catalyzed Hydrazine‐Directed CH Activation: Redox‐Neutral and Traceless by NN Bond Cleavage1. Issue 47 (25th September 2013) - Zhao, Dongbing; Shi, Zhuangzhi; Glorius, Frank
<x xml:space="preserve">Abstract</x> Fishing for complements! There is an alternative to the useful Fischer indole synthesis. The new method utilizes the same retrosynthetic disconnection but is based on a RhIII‐catalyzed directed CH activation step and a successive coupling with alkynes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>